Local Culture And Subjective Well-Being Among Msme Actors In East Java: A Qualitative Study - Syamsul Arifin; abdul Tholib Bon; Mahmud Ismail (CV Pena Jaya Pers, 2026)
Purpose: This study aims to explore how local culture contributes to the subjective well-being of Micro, Small, and Medium Enterprise (MSME) actors in East Java, Indonesia. Design/methodology/approach: This study employs a qualitative case study approach to explore the experiences and perceptions of MSME actors regarding the relationship between local cultural values and subjective well-being. Data are intended to be collected through semi-structured interviews, observations, and documentation involving MSME owners and workers in selected areas of East Java. Data analysis follows an interactive qualitative analysis process involving data condensation, data display, and conclusion drawing. Findings: The study is designed to examine several dimensions of local culture that may contribute to subjective well-being, including social relationships, mutual cooperation, local values, community support, cultural identity, and meaning derived from economic activities. The empirical findings should be finalized bsed on the actual interview and observation data collected from MSME actors. Research limitations/implications: The study focuses on MSME actors in East Java and therefore requires careful consideration when transferring the findings to other regions or economic groups. Future research may employ comparative studies across regions or integrate quantitative measures of subjective well-being. implications: The study is expected to provide insights for MSME development programs by demonstrating the importance of incorporating local cultural values, social relationships, and community-based approaches into economic empowerment policies. Originality/value: This study contributes to the literature by positioning local culture as an important contextual factor in understanding subjective well-being among MSME actors. Rather than viewing MSME welfare solely from an economic perspective, the study emphasizes the subjective and culturally embedded dimensions of well-being. Paper type: Qualitative Case Study